2023
DOI: 10.1200/jco.23.00911
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Oligometastatic Breast Cancer

Lajos Pusztai,
Mariya Rozenblit,
Peter Dubsky
et al.

Abstract: De novo oligometastatic breast cancer, a unique disease needing new treatment paradigms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Five patients in this study had de-novo stage-IV (metastatic) disease. Clinical and molecular analyses have shown that metastatic disease often shares molecular similarities with primary tumors [ 31 ], and four of these patients had G ≥ 2 therapeutic responses, which can be explained by the activation of NK-mediated antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients in this study had de-novo stage-IV (metastatic) disease. Clinical and molecular analyses have shown that metastatic disease often shares molecular similarities with primary tumors [ 31 ], and four of these patients had G ≥ 2 therapeutic responses, which can be explained by the activation of NK-mediated antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%